Mitochondrial Markers for Cancer: Relevance to Diagnosis, Therapy, and Prognosis and General Understanding of Malignant Disease Mechanisms. (18th November 2012) - De Paepe, Boel
Abstract : Cancer cells display changes that aid them to escape from cell death, sustain their proliferative powers, and shift their metabolism toward glycolytic energy production. Mitochondria are key organelles in many metabolic and biosynthetic pathways, and the adaptation of mitochondrial function has been recognized as crucial to the changes that occur in cancer cells. This paper zooms in on the pathologic evaluation of mitochondrial markers for diagnosing and staging of human cancer and determining the patients' prognoses.